Viruses occurring in watermelon in the tropical lowland of the Tocantins state, Brazil - Tavares, Aline Torquato; Silva, Edgard Henrique Costa; Ferreira, Tiago Alves; Marques, Kleycianne Ribeiro; Nascimento, Ildon Rodrigues (Revista de Ciências Agro-Ambientais, 2017)
The cucurbits are subject to various diseases caused by viruses and the identification of species that predominate in one region has great importance to direct the control strategies. The study aimed to diagnose by DAS-ELISA and RT-PCR tests virus isolates collected in commercial plantations of lowland tropical watermelon in the State of Tocantins. Were collected 20 leaf in the municipality of Formoso do Araguaia and 46 leaf samples from Lagoa da Confusão. The samples were packed in plastic bags properly identified and transferred to the Department of Plant Pathology DFP / UFLA and / or stored in a refrigerator at -80 °C. The samples were grown in a greenhouse for plants pumpkin Curcubita pepo cv. Caserta and were performed the DAS-ELISA test serology and molecular evaluation. No sample reacted with the antiserum for the cucumber mosaic virus (CMV), on the other hand reacted to sixteen mosaic virus-of-pumpkin (SqMV). The predominant virus in producing regions of watermelon grown in lowland tropical rainforest in the state of Tocantins were ZYMV and SqMV and the occurrence of mixed infection (ZYMV+SqMV) was achieved in 35% of samples in the municipality of Lagoa da Confusão. In the municipality of Formoso do Araguaia prevailed ZYMV.